EXPERIENCE OF ADMINISTRATION OF HUMAN MONOCLONAL ANTIBODIES TO TNF IN PATIENT WITH JUVENILE RHEUMATOID ARTHRITIS WITH UVEITIS - A.O. Lisitsin (Voprosy Sovremennoj Pediatrii, 2009)
The article presents a case report of severe juvenile rheumatoid arthritis with uveitis, refractory to treatment with classic immuno-suppressants and chimeric monoclonal antibodies to the tumor necrotizing factor ?. Successful administration of biological agent adalimumab was described: morning joints stiffness and exudative lesions in affected joints was completely stopped up to the 4th week of treatment, the range of motions was increased significantly. Laboratory indices of disease activity (ESR, C-reactive protein in plasma) were normalized to 6th week. Treatment with adalimumab induced the development of remission of subacute bilateral uveitis. Key words: children, juvenile rheumatoid arthritis, rheumatoid arthritis, treatment, adalimumab. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(6):151-157)